EFEKTIFITAS MEDIA AUDIO VISUAL (ANIMASI TAYO) TERHADAP KEMAMPUAN MENYIMAK ANAK 5-6 TAHUN - Jusnidar, Jusnidar; Safirah, Nur Adillah; Usman, Usman; Ilyas, Sitti Nurhidayah; Musi, Muhammad Akil (Information Technology Education Department, 2024)
This study aims to determine the effectiveness of using audio visual media (Tayo Animation) on the listening ability of children aged 5-6 years old in Early Childhood Education DWP LPMP South Sulawesi. The research method used is a quantitative method with a Quasi Experimental Design research type. The population in this study were students at the Early Childhood Education DWP LPMP South Sulawesi, total 24 children. The sampling in this study is purposive sampling. The sample in this study consisted of 12 children with the division of 6 children as the experimental group and 6 children as the control group. The analysis techniques used are descriptive statistical analysis and non-parametric analysis. Based on the results of the study, it can be concluded that the listening ability of children who were given treatment using audio visual media (Tayo Animation) in the experimental group was more effective than the control group who were not given treatment. So, it can be concluded that the use of audio-visual media (Tayo Animation) provides significant effectiveness on the listening ability of children aged 5-6 years old in Early Childhood Education DWP LPMP South Sulawesi.